ELECTROCHEMICAL EVALUATION OF THE RELATIONSHIP BETWEEN THE THERMAL TREATMENT AND THE PROTECTIVE PROPERTIES OF THIN SILICA COATINGS ON ZINC SUBSTRATES - OVÁRI, Tamara-Rita; KATONA, Gabriel; SZABÓ, Gabriella; MURESAN, Liana Maria (Studia Universitatis Babeș-Bolyai Chemia, 2022)
One of the challenges of smart and thin silica layers preparation on metallic substrates consists in the simultaneous network formation and introduction of corrosion inhibitors in it. Taking into account that both steps are affected by the temperature, it is really important to evaluate first its effect on the silica network formation. In this context, this paper aims the presentation of findings regarding the optimal heat treatment parameters in the preparation of thin silica (SiO2) coatings on zinc. These silica layers were prepared by sol-gel method (dip-coating technique) and were tested as protective films against zinc (Zn) corrosion. After optimization of several parameters such as the drying temperature, drying duration, the corrosion resistance of the coatings was evaluated mainly by means of electrochemical methods (electrochemical impedance spectroscopy and potentiodynamic polarization). The electrochemical evaluation corroborated with morpho-structural characterization led to the conclusion that the SiO2 coatings have better protection properties when dried at 150°C for 1h.